Development of Picture Storybooks to Improve Elementary School Students' Reading Literacy - Sayidiman; Al. Dina Syarila Rasya (Sains Global Institut, Indonesia, 2026)
This study aims to examine the development of illustrated storybooks as learning media to improve reading literacy among elementary school students. The research employed a literature review approach by analyzing various scientific journals, books, and relevant academic sources related to reading literacy, learning media, and illustrated storybooks in elementary education. Data were collected through documentation of various literature sources and analyzed using descriptive qualitative methods. The findings indicate that the use of illustrated storybooks can enhance students’ reading interest, reading comprehension, learning motivation, and language skills. Illustrated storybooks also help students understand learning materials more concretely through the combination of text and engaging visual illustrations. Furthermore, the development of illustrated storybooks that are aligned with the characteristics of elementary school students can create a more enjoyable and interactive learning environment. Therefore, the development of illustrated storybooks is considered a suitable learning medium to support the improvement of literacy culture in elementary schools.